PTP1B inhibitors from Isodon ternifolius collected in Vietnam - Pham, Minh Quan; Le, Thi Huong Thuy; Do, Thi Thuy; To, Dao Cuong; Pham, Quoc Long; Hung, Nguyen Phi (Vietnam Journal of Science and Technology, 2020)
From the whole plant of Isodon ternifolius collected in Vietnam, four triterpens including ursaldehyde (1), ursolic acid (2), b-sitosterol (3) and b-sitosteryl ferulate (4) were purified. Their chemical structures were determined by interpretation of NMR and MS data and comparison with the literatures. Compounds 1-4 were evaluated for their inhibitory activity against PTP1B enzyme activity using in vitro assay. Compounds 1 and 2 displayed potential activities with IC50 values of 16.92 ± 0.12 and 3.42 ± 0.45 μM, respectively. This is the first time that compounds 1 and 4 have been isolated from the Isodon genus and I. ternifolius has been evaluated for the PTP1B inhibitory activity.